2014
DOI: 10.1007/s11356-014-2671-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term cattle manure application on soil properties and soil heavy metals in corn seed production in Northwest China

Abstract: To evaluate the effects of manure application on continuous maize seed production, 10-year cattle manure on soil properties, heavy metal in soil and plant were evaluated and investigated in calcareous soil. Results showed that manure application increased soil organic matter, total and available nutrients, pH, and electrical conductivity (EC), and the most massive rate caused the highest increase. Manure application led to an increase in exchangeable fraction and an increase of availability of heavy metal. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 62 publications
6
55
3
Order By: Relevance
“…In general, EDTA and manures increase the sol-exch fraction and available forms of heavy (Song et al 2016) which was consistent with the results of this study. In another study, cattle manures have been also shown to increase the availability of heavy metals in soil (Zhao et al 2014). Therefore, the toxicity of the heavy metals in cathodic soil might be one of the main driving factors for the reduction of soil microbial variables which further was supported by our results in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, EDTA and manures increase the sol-exch fraction and available forms of heavy (Song et al 2016) which was consistent with the results of this study. In another study, cattle manures have been also shown to increase the availability of heavy metals in soil (Zhao et al 2014). Therefore, the toxicity of the heavy metals in cathodic soil might be one of the main driving factors for the reduction of soil microbial variables which further was supported by our results in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies have indicated that manures and their extracts including CME and PME solubilize heavy metals leading to increase the heavy metals in the sol-exch and available forms (de la Fuente et al 2011;Indoria et al 2013;Zhao et al 2014). However, the solubilizing effects of CME and PME were less than that of EDTA in the current study which was also supported by our complementary studies Safari Sinegani 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatases play a meaningful role in P cycling, because they provide P for plant uptake by releasing PO 4 from immobile organic P. The significantly greater activity of alkaline phosphatase in manure and straw residues treated soil could be attributed to enhanced microbial activity [43]. Manure into soil also resulted in changes in origin, states, and/or persistence of enzymes in soil [44]. Due to the positive relationship between TN and SOC in topsoil, our results correspond to Saha et al that cellulose showed a strong positive correlation with alkaline phosphatase in the alkali environment [42].…”
Section: Statistical and Canonical Correspondence Analysismentioning
confidence: 99%
“…*Significant difference (P < 0.05) between ecotypes conditions of soils, thereby promoting plant growth (Clemente et al 2012;Bolan et al 2014;Zhao et al 2014). Tailings are poor in nutrients, but rich in heavy metals, which affect nutrient uptake (Meeinkuirt et al 2013;Li et al 2014).…”
Section: Discussionmentioning
confidence: 99%